2014
DOI: 10.1159/000363142
|View full text |Cite
|
Sign up to set email alerts
|

VEGF mRNA Assessment in Human Pterygium: A New ‘Scope' for a Future Hope

Abstract: Purpose: The lack of powerful evidence to support the efficacy of anti-vascular endothelial growth factor (VEGF) therapy in human pterygium can be attributed to incomplete VEGF expression assessment by restrictive use of immunohistochemistry only and failure to use the molecular methods able to confirm immunohistochemical findings. By adding at least one more sensitive method to assess human pterygium VEGF expression, a more accurate selection of patients for bevacizumab therapy could be done and this would im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent research found that miR-21/vascular endothelial growth factor (VEGF) plays an important role in the development of ocular angiogenesis [37]. Previous studies showed that anti-VEGF therapy was effective in some patients with pterygium [38] taking into account that miR-21 is the relative upstream factor and anti-miR-21 may be a possible treatment strategy for pterygium. Of course, a delivery system is required to ensure stability in vivo and to efficiently and safely introduce nucleic acid–based drugs into cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found that miR-21/vascular endothelial growth factor (VEGF) plays an important role in the development of ocular angiogenesis [37]. Previous studies showed that anti-VEGF therapy was effective in some patients with pterygium [38] taking into account that miR-21 is the relative upstream factor and anti-miR-21 may be a possible treatment strategy for pterygium. Of course, a delivery system is required to ensure stability in vivo and to efficiently and safely introduce nucleic acid–based drugs into cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of pterygium is still unclear, chronic inflammation, angiogenesis, and uncontrolled proliferation seem to be the key mechanisms in progression (1,5,20). Several inflammatory and angiogenic factors, such as VEGF, MMP, and TGF, were suggested to be related to its pathogenesis (21)(22)(23). In the present study, we investigated the cell expressions of COX-2 and CXCR-4 in pterygium tissue.…”
Section: Discussionmentioning
confidence: 94%
“…The detection sensitivity of the RNAscope method has been proven by using positive (POLR2A) and negative controls (probes against the bacterial dap B gene), evaluated using the same protocol applied in our previous studies [ 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization techniques were applied on human placenta tissue [31] but not for the detection and characterization of PDPN expression/distribution in the stromal and epithelial components of the human placenta. Among these methods, RNAscope is a commercially accessible in situ hybridization (ISH) technique used to identify RNA in formalin-fixed paraffin-embedded tissue [13,[32][33][34]. This technique enables the visualization of single RNA molecules within individual cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation